Directions of Stimulation of the Development of Tourism Infrastructure by Attraction of Investments - SADYKOV, Zhassulan; KHAMITOVA, Dariga; KAZAKBAYEVA, Turdibuvi; AKIZHANOVA, Aigerim; NAKHIPBEKOVA, Symbat; KHASSENKHANOV, Nurshuak (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).12, 2022)
This article notes that the uncertainty of the consequences of the pandemic has shown the need for the development of domestic tourism, the creation of modern health resort and tourism services and improving the quality of tourism infrastructure by attracting investments for maintenance and provision of transport and the development of tourism products and services, the introduction of environmental protection measures. Using the given statistical data on the development of the tourism and hospitality industry of the Republic of Kazakhstan, the authors analyzed the influence of some factors influencing the development of the tourism industry. The indicators of the structure of the population's expenditures on paid services, the distribution of resident visitors by purpose of travel at places of accommodation for 202 1 , the number of visitors served at places of accommodation for tourists in general in Kazakhstan, the main indicators of financial and economic activities in the field of tourism for 2016-202 1 are given, performance indicators of tourist infrastructure facilities for the analyzed period. Proposals are given for the transformation of the most significant tourist sites included in the Touristification Map of Kazakhstan into one tourist cluster with a unique dominant experimental structure with transfer to foreign tourism markets in the future.